Pomocy daje 5 gwiazdek



Pomocy Daje 5 Gwiazdek class=

Odpowiedź :

Heh

Odpowiedź:

[tex]\sqrt{7^{5}}*7^{-\frac{3}{2}}=(7^{5})^{\frac{1}{2}}*7^{-\frac{3}{2}}=7^{\frac{5}{2}}*7^{-\frac{3}{2}}=7^{\frac{5}{2}+(-\frac{3}{2})}=7^{\frac{2}{2}}=7^{1}=7[/tex]

[tex]9^{-\frac{3}{4}}:27^{-\frac{3}{2}}=(3^{2})^{-\frac{3}{4}}:(3^{3})^{-\frac{3}{2}}=3^{-\frac{3}{2}}:3^{-\frac{9}{2}}=3^{-\frac{3}{2}-(-\frac{9}{2})}=\\ \\=3^{-\frac{3}{2}+\frac{9}{2}}=3^{\frac{6}{2}}=3^{3}=27[/tex]

Szczegółowe wyjaśnienie:

Rozwiązanie w załączniku
Zobacz obrazek Iknbil1